Secukinumab demonstrates high and sustained efficacy in nail psoriasis: Post hoc analysis from phase 3 trials in patients with psoriatic arthritis - Reich, K; Baraliakos, X; Coates, LC; Elewski, B; Bao, W; Kasparek, T; Gaillez, C; Pournara, E; Aassi, M; Perella, C; Gottlieb, AB (Wiley, 2022)
Secukinumab showed consistent and sustained efficacy in clearing nail psoriasis in patients with psoriatic arthritis, with or without axial manifestations, irrespective of severity of nail involvement. Reduction of nail disease was also associated with response across all musculoskeletal and skin manifestations of psoriatic arthritis.